THE CORRELATION BETWEEN STUDENTSâ GRAMMAR MASTERY AND THEIR ABILITY IN ARRANGING JUMBLED WORDS INTO GOOD SENTENCE - MAHENDRA, OKTA; THRESIA, FENNY (Sriwijaya University Learning and Education International Conference, 2016)
The objective of this research is to know the correlation between studentsâ grammarmastery and their ability in arranging jumbled words into good sentence at the fifthsemester of English Education Study Program Muhammadiyah University of Metroacademic year 2015/2016. This research is quantitative research. The population inthis research is fifth semester of English Study Education Program MuhammadiyahUniversity Academic Year 2015/2016. The researcher used saturated sampling; allof the students at fifth semester. with amount 45 students. The data collectingtechnique used are the test of grammar mastery especially at simple simple pasttense and the test of ability in arranging jumbledd words into good sentence. Theresearcher used Lilliefors formula to test the normality of the research and ProductMoment Correlation to test the hypothesis. Based on the data analysis, theresearcher finds there is correlation between studentsâ grammar mastery and theirability in arranging jumbledd words into good sentence with coefficient xy r = 0,97.This value is consulted by rtable =0,294 and the result is 0,97>0,294, therefore there iscorrelation between X variable and Y variable. The conclusion, there is correlationbetween studentsâ grammar mastery especially at simple simple past tense and theirability in arranging jumbledd words into good sentence at fifth semester inMuhammadiyah University of Metro academic year 2015/ 2016.